Dose dependent effect of pregnant mare serum gonadotropin and human chorionic gonadotropin on in vitro maturation of goat oocytes - KOUAMO, J; KHARCHE, S D (The Indian Journal of Animal Sciences, 2014)
This study was aimed to evaluate the dose dependent effect of pregnant mare serum gonadotropin and human chorionic gonadotropin on in vitro maturation goat oocytes. The study was planned in 2 experiments. In the first experiment effect of pregnant mare serum gonadotropin supplementation on nuclear maturation of goat oocytes using 5 different concentrations of PMSG, was studied. The treatment was divided into group 1 (control medium containing TCM-199, sodium pyruvate (0.25mM), gentamycin (50µg/ml), L-glutamine (100µg/ml), estradiol 17-ß (1µg/ml), BSA (3mg/ml), supplemented with 10% FBS); group 2 (control medium + 10 IU/ml PMSG); group 3 (control medium + 20 IU/ml PMSG); group 4 (control medium + 30 IU/ml PMSG); group 5 (control medium + 40 IU/ml PMSG); and group 6 (control medium + 50 IU/ml PMSG). The oocytes of these treatment groups were matured in maturation media for 27 h in humidified atmosphere of 5% CO2 at 38.5°C in a CO2 incubator. The maturation rates achieved in groups 1–6 were 20.0, 48.51, 74.63, 74.15, 75.0 and 76.33%, respectively. In experiment 2, the effect of hCG supplementation on nuclear maturation of goat oocytes using 3 different concentrations of PMSG, was studied. Second experiment was divided into group 1 (control medium + 20 IU/ml PMSG +10IU/ml hCG), group 2 (control medium + 20 IU/ml PMSG +20IU/ml hCG) and group 3 (control medium + 20 IU/ml PMSG +30IU/ml hCG). The maturation rates achieved in groups 1–3 were 77.0, 85.19 and 84.22%, respectively. It can be concluded that supplementation of 20 IU/mL PMSG and 20IU hCG in maturation media significantly increased the maturation rate.